2023
DOI: 10.1021/acsomega.3c02179
|View full text |Cite
|
Sign up to set email alerts
|

Quinolizidine-Type Alkaloids: Chemodiversity, Occurrence, and Bioactivity

Abstract: Quinolizidine alkaloids (QAs) are nitrogen-containing compounds produced naturally as specialized metabolites distributed in plants and animals (e.g., frogs, sponges). The present review compiles the available information on the chemical diversity and biological activity of QAs reported during the last three decades. So far, 397 QAs have been isolated, gathering 20 different representative classes, including the most common such as matrine (13.6%), lupanine (9.8%), anagyrine (4.0%), sparteine (5.3%), cytisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 278 publications
1
3
0
Order By: Relevance
“…4d). Our results confirm the intermediacy of (−)-sparteine in relation to (+)-lupanine and its derivatives, which has not been clear in recent depictions of the general QA pathway 32, 33 .…”
Section: Mainsupporting
confidence: 84%
“…4d). Our results confirm the intermediacy of (−)-sparteine in relation to (+)-lupanine and its derivatives, which has not been clear in recent depictions of the general QA pathway 32, 33 .…”
Section: Mainsupporting
confidence: 84%
“…Oxymatrine is a quinolizidine alkaloid compound that has been shown in numerous studies to have various beneficiary functions, including antioxidant effects; antiinflammatory, antiviral, and anticancer activities; immune system regulation; cardiovascular improvement; and nervous system protection [33][34][35][36][37]. It can activate the Nrf2 pathway and enhance antioxidant enzymes [39,40]. Several studies have reported that OM treatment could improve ischemia/reperfusion and liver failure through the Nrf2/ho-1 pathway [30,31,41].…”
Section: Discussionmentioning
confidence: 99%
“…Sophora alopecuroides L. (Fabaceae family, Sophora genus) is widely distributed over a large area of northwestern China and southern Russia. , This plant has long been used in heart disease, treating fever, bacterial infection, rheumatism, and gastrointestinal diseases in traditional Chinese medicine. Phytochemical investigations have shown that S. alopecuroides contains quinolizidine alkaloids (QAs, matrine-, cytisine-, anagyrine-, thermopsine-, and aloperine-types), flavonoids, polysaccharides, and steroids. , Among these compounds, aloperine, which was first isolated in 1935 from the leaves and seeds of S. alopecuroides, , has been extensively researched and has displayed good bioactivity.…”
Section: Introductionmentioning
confidence: 99%